How to do this proving question:
Use the trigonometric identity of the sum of cosines:& cos a + cos b = 2 cos (a+b)/2& cos (a-b)/2.
cos x + cos 3x + cos 5x + cos 7x = 2 cos(x+3x)/2 cos(x-3x)/2 & + 2 cos(5x + 7x)/2 cos( 5x - 7x)/2 = = 2 cos 2x cos x + 2 cos 6x& cos x = 2 cosx (cos 2x + cos 6x) = 4 cos x * cos (2x + 6x)/2& * cos(2x - 6x)/2 = = 4 cos x * cos 4x * cos 2x
It’s the most wonderful time of the year: Winter Holidays! Thanksgiving dinner was served, Black Friday has finished, and now…
APPROVED BY CLIENTS
The service provided was outstanding. The completed assignment was finished and emailed by the deadline, without having to request any revisions. I would definitely use the service again and would recommend it to students at any level.